Hubungan Tingkat Konsumsi Energi Dan Protein Dengan Ketahanan Fisik Atlet Sepak Bola Ps Barito Putera Tahun 2014 - Firyal Yasmin; Magdalena Magdalena; M. Syarif; STIKES Husada Borneo; Poltekes Banjarbaru; Alumni STIKES Husada Borneo (Jurnal Kesehatan Indonesia, 2015)
PS Barito Putera is a professional football club in Indonesia and came from Banjarmasin, South Kalimantan. In football, not only training methods or talent that will determine the achievements that can be achieved by an athlete, but the intake of proper nutrients will also have a positive influence on the improvement of performance and achievements that can be achieved by an athlete. The aims of this study is to determine the level of energy and protein consumption by football players who are then linked to the level of physical endurance. This research uses the analytical method with cross sectional design. This study conducted on 24 respondents PS Barito Putera football athletes. Result in this research is the group age responden agest 24-27 years old (50%), the weight respondent about 66-75 kg (62,5%), the tall respondent about 165-175 cm (58,33%), the responden who has parents an athlete is 25%, and respondent who consumption vitamin and mineral suplemen is 91,67%. The most responden of consumption energy level is normal chategory (68,33%), the most consumption protein level is normal chategory (62,5%), and the most responden of physical endurance level is average chategory (54,17%). Results of statistical tests by using spearman’s shows, levels of energy consumption obtained p=0,007 and levels of protein intake obtained p=0,014, which means there is a correlation between energy and protein consumption with the level of physical endurance athlete football PS Barito Putera in 2014.